Cohort analysis of outcomes in 69 490 emergency general surgical admissions across an international benchmarking collaborative. Issue 3 (8th March 2017) - Chana, Prem; Joy, Mark; Casey, Neil; Chang, David; Burns, Elaine M; Arora, Sonal; Darzi, Ara W; Faiz, Omar D; Peden, Carol J
Abstract : Objective: This study aims to use the Dr Foster Global Comparators Network (GC) database to examine differences in outcomes following high-risk emergency general surgery (EGS) admissions in participating centres across 3 countries and to determine whether hospital infrastructure factors can be linked to the delivery of high-quality care. Design: A retrospective cohort analysis of high-risk EGS admissions using GC's international administrative data set. Setting: 23 large hospitals in Australia, England and the USA. Methods: Discharge data for a cohort of high-risk EGS patients were collated. Multilevel hierarchical logistic regression analysis was performed to examine geographical and structural differences between GC hospitals. Results: 69 490 patients, admitted to 23 centres across Australia, England and the USA from 2007 to 2012, were identified. For all patients within this cohort, outcomes defined as: 7-day and 30-day inhospital mortality, readmission and length of stay appeared to be superior in US centres. A subgroup of 19 082 patients (27%) underwent emergency abdominal surgery. No geographical differences in mortality were seen at 7 days in this subgroup. 30-day mortality (OR=1.47, p<0.01) readmission (OR=1.42, p<0.01) and length of stay (OR=1.98, p<0.01) were worse in English units. Patient factors (age, pathology, comorbidity) were significantly associated with worse outcome as were structural factors, including low intensive care unit bed ratios, high volume and interhospital transfers. Having dedicated EGS teams cleared of elective commitments with formalised handovers was associated with shorter length of stay. Conclusions: Key factors that influence outcomes were identified. For patients who underwent surgery, outcomes were similar at 7 days but not at 30 days. This may be attributable to better infrastructure and resource allocation towards EGS in the US and Australian centres.